Boru pracārayaṭa Samasamājayen pilituru - Weerakoon, R. (Laṅkā Kamkaru Sammēlanaya, 1978)
A rejoinder to charges of alleged counter revolutionary acts of the Lanka Sama Samaja Party in the politics of Sri Lanka.